The watchmaker's hand [compact disc, unabridged] - Deaver, Jeffery (Penguin Audio, 2023)
When a New York City construction crane mysteriously collapses, causing mass destruction and killing several people, Rhyme and Amelia Sachs are on the case. A political group claims to be behind the sabotage and threatens another crane collapse in twenty-four hours, unless their demands are met. The clock is ticking. With New York in a panic, the stakes are higher than ever for Rhyme and his team to unravel the plot before the timer runs out and more cranes crash down, reducing the city and its people to rubble. Then Rhyme realizes that the mastermind behind the terror is his own nemesis the Watchmaker.